Evaluating the impact of green SCOR and ISO 14001: Based practices on sustainability in palm oil supply chains - Sonder, Johni; Meitiana, Meitiana; Sambung, Roby; Kristinae, Vivy; Christa, Usup Riassy (Trigin Publisher, 2025)
This study aims to assess the effectiveness of environmentally conscious practices in the palm oil industry’s supply chain by integrating the Green SCOR model with ISO 14001-based environmental indicators. A case study was conducted in a government-owned palm oil refinery in Central Kalimantan, Indonesia. The research employs a mixed-method approach involving surveys, interviews, and the Analytical Hierarchy Process (AHP) using Expert Choice software to weight and prioritize 24 Key Performance Indicators (KPIs). The results indicate that environmental management performance reached a satisfactory level of 83.51%, with the most critical indicators being related to waste quality monitoring and hazardous waste (B3) disposal. These findings underscore the importance of aligning supply chain operations with environmental management standards to ensure regulatory compliance and sustainability. The integration of ISO 14001 and Green SCOR enhances the accuracy and comprehensiveness of environmental performance assessments. The study concludes that periodic re-evaluation and the inclusion of broader environmental metrics are essential to maintain long-term sustainability in industrial operations. Future research should explore stakeholder involvement and dynamic data integration for more adaptive environmental strategies.